Mutualistic fungal endophytes in the Triticeae – survey and description. Issue 1 (21st January 2014) - Card, Stuart D.; Faville, Marty J.; Simpson, Wayne R.; Johnson, Richard D.; Voisey, Christine R.; de, Anouck C. M.; Hume, David E.
Abstract Grasses of the tribe Triticeae were screened to determine the presence of mutualistic epichloae fungal endophytes. Over 1500 accessions, from more than 250 species, encompassing 22 genera within the Triticeae were screened using immunodetection and direct staining/microscopy techniques. Only two genera, Elymus and Hordeum, were identified as harbouring epichloae endophytes with accessions native to a range of countries including Canada, China, Iran, Kazakhstan, Kyrgyzstan, Mongolia, Russia and the USA. Genetic analysis based on simple sequence repeat data revealed that the majority of endophytes cluster according to geographical regions rather than to host species; many strains isolated from Hordeum grouped with those derived from Elymus, and amongst the Elymus‐derived strains, there was no clear correspondence between clustering topology and host species. This is the first detailed survey demonstrating the genetic diversity of epichloae endophytes within the Triticeae and highlights the importance of germplasm centres for not only preserving the genetic diversity of plant species but also the beneficial microorganisms they may contain.